An efficient synthesis of carboranyl tetrazoles via alkylation of 5-R-1H-tetrazoles with allylcarboranes. (5th September 2016) - Ol'shevskaya, Valentina A.; Makarenkov, Anton V.; Kononova, Elena G.; Peregudov, Alexander S.; Lyssenko, Konstantin A.; Kalinin, Valery N.
Graphical abstract: The regioselective synthesis of new o - and m -carborane tetrazoles was developed via the alkylation of 5-R-1H-tetrazoles with available allylcarboranes. Abstract: An efficient triflic acid catalyzed regioselective alkylation of 5-R-1H-tetrazoles with readily available allylcarboranes is reported. The suggested synthetic procedure allows the formation of a variety of carboranyl-substituted tetrazoles in a good yield under mild conditions. Transformations of newly synthesized carboranyl tetrazoles under UV irradiation were studied. Allylcarboranes as starting materials were prepared via Pd-catalyzed cross-coupling reaction of iodocarboranes with allylmagnesium bromide.